Integrating Web-Based Interactive Multimedia and Problem-Based Learning to Support Social Studies Instruction in Junior High Schools - Emi Susanti; Yamanto Isa; Leni Pebriantika (Sakura Digital Nusantara, 2026)
This study addresses the low student engagement and limited availability of interactive learning media in Social Studies, specifically concerning the topics of scarcity and human needs at SMP Negeri 13 OKU. The primary objective was to develop and evaluate a web-based interactive multimedia platform using Canva, integrated with a Problem-Based Learning (PBL) approach. Using the Research and Development (R&D) method with the ADDIE model, the research produced a digital learning tool that incorporates text, images, audio, video, and interactive features. Validation results from experts confirmed the product’s high quality, placing it in the 'Excellent' category for validity. Furthermore, field testing achieved high practicality scores (89.6%), indicating significant student interest. These findings conclude that the PBL-based interactive multimedia is a valid and practical tool that shows strong potential to foster an active learning atmosphere and support the development of critical thinking in the Social Studies classroom